2010
DOI: 10.1073/pnas.1010830107
|View full text |Cite
|
Sign up to set email alerts
|

Culture, distress, and oxytocin receptor polymorphism (OXTR) interact to influence emotional support seeking

Abstract: Research has demonstrated that certain genotypes are expressed in different forms, depending on input from the social environment. To examine sensitivity to cultural norms regarding emotional support seeking as a type of social environment, we explored the behavioral expression of oxytocin receptor polymorphism (OXTR) rs53576, a gene previously related to socio-emotional sensitivity. Seeking emotional support in times of distress is normative in American culture but not in Korean culture. Consequently, we pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
242
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(272 citation statements)
references
References 34 publications
(41 reference statements)
23
242
2
Order By: Relevance
“…We speculate that the OXTinduced increase in prefrontal cortex activity may also reflect social support seeking (Sherman et al, 2009). Interestingly, an OXTR polymorphism has been linked to social support seeking, but the direction of this effect was dependent on cultural norms (Kim et al, 2010). Likewise, the interaction between OXT and gonadal steroids could cause increased or decreased OXT effects depending on the social domain.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the OXTinduced increase in prefrontal cortex activity may also reflect social support seeking (Sherman et al, 2009). Interestingly, an OXTR polymorphism has been linked to social support seeking, but the direction of this effect was dependent on cultural norms (Kim et al, 2010). Likewise, the interaction between OXT and gonadal steroids could cause increased or decreased OXT effects depending on the social domain.…”
Section: Discussionmentioning
confidence: 99%
“…Another consideration neglected in this study is the sensitivity of the oxytocinergic system to environmental factors. Studies indicates that maternal caregiving in animals [57] and cultural differences in humans [58] modulate the impact of OXTR variation on social behaviour. Lastly, association with risk for ASC needs to be investigated to support claims of this SNP's involvement in the psychopathological deficits exhibited in persons with the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…As prior research has identified inter-ethnic differences in OXTR rs53576, with greater proportions of GG individuals among Caucasians (Kim et al, 2010), a follow-up analysis tested a three-way interaction among genotype, stress, and ethnicity (European-American versus other). This interaction was not significant (p = .20), indicating no ethnic differences in the stress-buffering role of OXTR rs53576; moreover, the magnitude of the OXTR GG × stress interaction was very similar between Caucasians (IRR = 0.91) and those of other ethnic groups (IRR = 0.87).…”
Section: Oxtr and Stress Bufferingmentioning
confidence: 99%